A facile assay for zDHHC palmitoyl transferase activation elucidates effects of mutation and modification - Naoko Adachi; Douglas T. Hess; Takehiko Ueyama (Journal of Lipid Research)
At least 10% of proteins constituting the human proteome are subject to S-acylation by a long-chain fatty acid, thioesterified to a Cys thiol side chain. Fatty S-acylation (prototypically, S-palmitoylation) operates across eukaryotic phylogeny and cell type. S-palmitoylation is carried out in mammalian cells by a family of 23–24 dedicated zDHHC palmitoyl transferase enzymes, and mutation of zDHHCs is associated with a number of human pathophysiologies. Activation of the zDHHCs by auto-S-palmitoylation, the transthioesterification of the active site Cys by fatty acyl coenzyme A, is the necessary first step in zDHHC-mediated protein S-palmitoylation. Most prior in vitro assessments of zDHHC activation have utilized purified zDHHCs, a time- and effort-intensive approach, which removes zDHHCs from their native membrane environment. We describe here a facile assay for zDHHC activation in native membranes. We overexpressed hemagglutinin-tagged wild-type or mutant zDHHCs in cultured HEK293 cells and prepared a whole membrane fraction, which was incubated with fluorescent palmitoyl CoA (NBD-palmitoyl-CoA) followed by SDS-PAGE, fluorescence imaging, and Western blotting for hemagglutinin. We show by mutational analysis that, as assayed, zDHHC auto-S-palmitoylation by NBD-palmitoyl-CoA is limited to the active site Cys. Application of the assay revealed differential effects on zDHHC activation of posttranslational zDHHC modification and of zDHHC mutations associated with human disease, in particular cancer. Our assay provides a facile means of assessing zDHHC activation, and thus of differentiating the effects of zDHHC mutation and posttranslational modification on zDHHC activation versus secondary effects on zDHHC functionality including altered zDHHC interaction with substrate palmitoyl-proteins.